The impact of serum-free culture on HEK293 cells: From the establishment of suspension and adherent serum-free adaptation cultures to the investigation of growth and metabolic profiles - Jang, Mi; Pete, Ellen Sofie; Bruheim, Per (Frontiers in Bioengineering and Biotechnology, 2022)
Serum-free cultures are preferred for application in clinical cell therapy and facilitate the purification processes of bioproducts, such as vaccines and recombinant proteins. It can replace traditional cell culture - eliminating potential issues posed by animal-derived serum supplementation, such as lot to lot variation and risks of pathogen infection from the host animal. However, adapting cells to serum-free conditions can be challenging and time-consuming, and is cell line and medium dependent. In addition, the knowledge of the impact of serum-free culture on cellular metabolism is limited. Herein, we successfully established serum-free suspension and adherent cultures through two adaptation procedures for HEK293 cells in serum-free Freestyle 293 medium. Furthermore, growth kinetics and intracellular metabolic profiles related to central carbon metabolism were investigated. The entire adaptation procedure took one month, and high cell viability (>90%) was maintained throughout. The serum-free adherent culture showed the best growth performance, measured as the highest cell density and growth rate. The largest differences in metabolic profiles were observed between culture modes (adherent vs. suspension), followed by culture medium condition (control growth medium vs. serum-free medium). Metabolic differences related to the adaptation procedures were only seen in suspension cultures. Interestingly, the intracellular itaconate concentration was significantly higher in suspension cells compared to adherent cells. Furthermore, when the cells back-adapted from serum-free to serum-supplemented control medium, their metabolic profiles were immediately reversed, highlighting the effect of extracellular components on metabolic phenotype. This study provides strategies for efficient serum-free cultivation and deeper insights into the cellular responses related to growth and metabolism responses to diverse culture conditions.